Study on inertial characteristics of photoresistors in a physical workshop - Андреев, А.Н.; Андреева, О.Н. (Radiotekhnika, 2020)
The article describes a measuring complex based on the 32-bit STM32F103VET6 microcontroller for studying the lux-ampere (light), frequency and inertial characteristics of a photoresistor with different laws of recombination of nonequilibrium charge carriers arising under the influence of light. The developed complex is connected to a personal computer (smartphone) and allows to analyze the rise and fall edges of the photoresistor current, as well as to determine the lifetime of excess charge carriers at different illumination levels. Unlike traditional methods for measuring the parameters of photoresistors operating in a dynamic mode, the proposed measuring complex does not use an oscilloscope and a separate modulator of the luminous flux (generator or light interrupter), this made it possible to significantly reduce the size and cost of the complex, as well as automate the measurement process. To determine the frequency response of the photoresistor, it is proposed to use a frequency synthesizer, which allows, together with a digital-to-analog converter of the microcontroller, to form an amplitude-modulated light flux of the required frequency and modulation depth. The complex described in the work can be connected to the Internet using a Wi-Fi module based on an ESP8266 microcontroller, which allows conducting research in a remote mode. It is also possible to determine the parameters of the photoresistor at different values of the load resistance.